Penggunaan Metode Eksperimen Berbantuan Media Konkret Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas III SD Negeri 6 Subagan - Ni Made Suartini (Jayapangus Press, 2019)
This study aims to improve the learning process by improving Class III Learning Outcomes of Class III Students of SD Negeri 6 Subagan Odd Semester 2017/2018 Academic Year through